Are we starting to 'think family'? evidence from a case file audit of parents and children supported by mental health, addictions and children's services. (9th February 2022) - McCartan, Claire; Davidson, Gavin; Donaghy, Mary; Grant, Anne; Bunting, Lisa; Devaney, John; Duffy, Joe
Abstract : Key Practitioner Messages: Cases are complex and families can feel overwhelmed by the number of agencies and referrals involved. Systemic, family‐focused practice can lead to improved outcomes; this should be consistent across mental health, addictions and children's services. Efforts to promote interagency collaboration include: clear job descriptions; co‐locating services; home visits; interprofessional education; and joint training. Joint decision‐making can help acknowledge and value everyone's role and contribution. Better recording and sharing of data can support informed, complex decision‐making and optimise support services.